QUALITY OF WORK LIFE AND LIFELONG LEARNING AMONG WORKING ADULTS IN MALAYSIA: THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT (Malaysian Management Journal, 2021)
There has been a significantly increasing emphasis on the quality of interactions between employers and employees in the context of managerial and organisational studies in Malaysia. To encourage a desirable workforce, organisations often list factors associated with quality of work life, employee engagement, and lifelong learning as contributors to achieving optimal organisational goals. However, do quality of work life and employee engagement truly lead to employee disposition for lifelong learning? This paper aims to explore quality of work life and employee engagement as precursors to establishing a workforce that embraces lifelong learning. Structural Equation Modeling analysis was employed on 472 samples obtained from working adults holding different positions in various organisations in the country. The empirical results demonstrate that quality of work life leads to employee engagement, which in turn, positively contributes to lifelong learning. The results also suggest that employee engagement fully mediates the relationship between quality of work life and lifelong learning. This study provides a more in-depth understanding of what it takes to create a workforce that engages in continuous learning, and sets the tone for compelling narratives in rolling out organisational vision and mission for lifelong learning in Malaysia.